Comparison of clinical outcomes for different morphological scores of D5 and D6 blastocysts in the frozen-thawed cycle - Yaping Jiang; Rui Jiang; Hui He; Xinling Ren; Qiong Yu; Lei Jin (BMC, 2023)
Abstract Background Both embryo development speed and embryo morphology score played a significant role in frozen-thawed embryo transfer cycle (FET) outcomes. Most of the literature indicates that D5 embryos performed better than D6 embryos, although a few also indicate that there is no difference in clinical outcomes between D5 and D6 embryos. Clinically, D5 embryos are preferred for equal morphological scores. But how to choose embryos when the morphological score of D6 embryos is better than D5? Methods A retrospective study including 8199 frozen-thawed embryo transfers (FETs) was conducted to analyze patients who underwent IVF-FET from January 2018 to December 2020. Patients were divided into 8 groups according to the rate of embryonic development and morphological scores to compare pregnancy outcomes. We further compared clinical pregnancy outcomes and neonatal outcomes between BC embryos on day 5 (D5) and BA/BB embryos on day 6 (D6). Results Our study found no difference in clinical pregnancy rate (CPR) and live birth rate (LBR) between AA/AB blastocysts in D5 or D6 frozen blastocysts. However, for BA/BB/BC blastocysts, embryonic pregnancy outcome was significantly better in D5 than in D6. In our further analysis and comparison of BC embryos in D5 and BA/BB embryos in D6, we found no difference in clinical pregnancy outcomes and neonatal outcomes, but D6 BA/BB embryos had a higher rate of miscarriage. After adjusting for confounding factors, none of the indicators differed between groups. Conclusion Our study provides suggestions for embryo selection: AA/AB embryos are preferred, regardless of the embryo development day, and the second choice is BA or BB embryos on D5. BA/BB embryos in D6 had a higher miscarriage rate than BC embryos in D5 but were not statistically significant after adjusting for confounding factors.